In Vitro Effect of Degradation in Sacco in the Rumen on the Anthelmintic Properties of Parkia Biglobosa and Pterocarpus Erinaceus on Haemonchus Contortus - Dèdéhou, Vidjinnangni Fifamè Grâce Nadège; Babatoundé, Sévérin; Hounzangbé-Adoté, Mahulé Sylvie (European Scientific Journal, ESJ, 2018)
Parkia biglobosa and Pterocarpus erinaceus are traditionally used to treat various ailments including helminth infections. This study was undertaken to evaluate the effect of the rumen degradability on anthelmintic properties of the two plants and to examine the possible role of tannins and/or polyphenols on these properties. Hydro-acetone extracts of in sacco degradability residues of P. biglobosa pods and P. erinaceus leaves were screened in vitro to determine the possible anti-parasitic effects against eggs and infective larvae of Haemonchus contortus. In addition, the possible involvement of tannins and/or polyphenols was examined by comparing the levels of inhibition of larval migration obtained with the same extracts, after of not addition of PVPP. Extracts of both plants induced significant egg hatch inhibition (p < 0.001). The effects were dose and incubation period dependent. Extracts of both plants have shown again remarkable larval migration inhibition compared to the PBS (p < 0.05). The effect of incubation period was not significant (p > 0.05). These results suggest that the plants did not lose their anthelmintic properties after rumen degradation. The use of the PVPP indicated for almost all of the extracts that tannins and/or polyphenols are largely involved in the effect. Complementary investigations are necessary to understand the metabolism of these plants in the digestive tract of the animals.